Material and technological concept of the construction of a turboshaft engine with the application of isochoric combustion – CFD thermal analysis - Tarnawski , Piotr (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The paper presents the concept of a turboshaft engine with the application of isochoric combustion, along with its technological design and the selection of construction materials. The presented engine concept and construction design are based on a three-dimensional numerical CFD analysis. The first stage of analysis concerned the development of the construction of the valve timing system itself. This simplified model of the engine can be used for the experiential verification of the self-adjusting segmented ceramic sealing system, which is an integral part of the presented engine concept. The second stage of analysis concerned the development of the construction of a prototype engine. To ensure high engine efficiency, it was necessary to provide a high temperature of gas in combustion chambers, and at the same time limit heat losses. The application of ceramics, as a construction material for chambers and nozzles, was a choice since it is resistant to high temperatures. To reduce heat losses, the area of contact between hot engine components was limited. Moreover, the implementation of screens reduced heat transfer by radiation. Finally, polishing the surfaces facilitated a reduction of radiation coefficients. The analysis conducted demonstrated that it is possible to construct an engine with promising effective efficiency and ensure that materials work below permissible temperatures.